Acquired tetracycline resistance genes by transposons and virulence factors in enterococci recovered from overland and aquatic animals: A systematic review. (15th August 2021) - Mussa, Ebthag Almabruk Mohamed; Alsalahi, Abdulsamad; Aljaberi, Musheer A.; Jasni, Azmiza Syawani; Desa, Mohd Nasir Mohd; Al‐Mahdi, Abdullah Yahya Mohammed; Hamat, Rukman Awang
Abstract: Enterococci possess a high propensity to spread their resistance genes between intra‐ and inter‐species via mobile genetic elements. Potential reservoirs for acquiring antibiotic resistance genes by commensal and environmental bacteria, including enterococci, have raised significant public health concerns over recent decades. This concern is further complicated by the rampant use of tetracyclines in aquaculture and animals for therapeutic and chemoprophylactic purposes. This systematic review was conducted to elucidate the occurrence of tetracycline‐resistant enterococcal species, their resistomes and virulence determinants in faecal samples of aquatic and overland animals. The PubMed, Web of Science, ScienceDirect and Scopus databases were searched to retrieve relevant studies that matched the specific keywords. A total of 19 low‐bias studies were included. It was found that several tetracycline resistance genes such as tet (M), tet (L), and tet (M + L) genes encode for the ribosomal protection protein or for the efflux mechanism of tetracyclines in E. faecium, E. faecalis, E. hirae, E. durans, E . gallinarium and E. casseliflavus . Additionally, tet (M) and tet (M + L) or tet (M) genes were associated with transposons Tn 916 and/or Tn 5397 or Tn 1545 plus Tn 916, respectively. The acquisition of tet (M) and tet (M + L) genes may be assisted by transposons Tn 916 and/or Tn 5397 or Tn 1545 plus Tn 916 . In conclusion, tetracycline‐resistant enterococci recovered from aquatic and overland animals could further complicate the management of antibiotic‐resistant bacteria in both humans and animals. Thus, a concerted, multisectoral and transdisciplinary approach (One Health) is needed for active surveillance to be exacted and for better public health measures to be initiated in the future.